Sociopreneurship Sebagai Pilihan Karir Generasi Muda - Andi Sahrul Jahrir; Muhammad Syukur; Firdaus W Suhaeb (Journal on Education, 2024)
The demographics that occurred in this decade have had a significant influence on Indonesia's social, political, economic and cultural systems. Youth who are the drivers of the demographic bonus are quickly taking positions and roles in the world of employment and political platforms and ideals that intersect with the realm of capitalism. In taking a role in the flow of the economic system, some young people feel they have the potential and freedom to develop their business and personal potential through entrepreneurship. Furthermore, the younger generation is trying to take on the role of being a social entrepreneurial agent. Socioentrepreneurship is nothing new for some young people as the key to reducing the level of inequality in Indonesia. Apart from that, the emergence of the smart city trend is a challenge for the government to collaborate with the private sector and civil society to create a good social business ecosystem in villages. On the other hand, smart villages are an attractive output as a mainstreaming goal of sociopreneurship. Empowerment and the creative economy become a playing field for youth and society to carry out social business. Moreover, with its natural potential and international market share, history has always looked at the creative products of Indonesian youth. So, this is not difficult to achieve. This article is a partial summary of the author's experience interacting over several years with start-ups, creative economy entrepreneurs, the social business community and social entrepreneurs in society. From the results of this article, it was found that young people with a variety of very fast and sophisticated technologies are starting to view social business opportunities as a survival option amidst their limited ability to find work. Social entrepreneurship is one of the keys for Indonesia to accelerate rapid and equitable economic and social development.